Surgical and Trauma Capacity Assessment in Rural Haryana, India - Manisha B. Bhatia; Srivarshini C. Mohan; Kevin J. Blair; Marissa A. Boeck; Ashish Bhalla; Sristi Sharma; Irene Helenowski; Leah C. Tatebe; Benedict C. Nwomeh; Mamta Swaroop (Ubiquity Press, 2021)
Background: Trauma is a major global health problem and majority of the deaths occur in low- and middle-income countries (LMICs), at even higher rates in the rural areas. The three-delay model assesses three different delays in accessing healthcare and can be applied to improve surgical and trauma healthcare delivery. Prior to implementing change, the capacities of the rural India healthcare system need to be identified. Objective: The object of this study was to estimate surgical and trauma care capacities of government health facilities in rural Nanakpur, Haryana, India using the Personnel, Infrastructure, Procedures, Equipment and Supplies (PIPES) and International Assessment of Capacity for Trauma (INTACT) tools. Methods: The PIPES and INTACT tools were administered at eight government health facilities serving the population of Nanakpur in June 2015. Data analysis was performed per tool subsection, and an overall score was calculated. Higher PIPES or INTACT indices correspond to greater surgical or trauma care capacity, respectively. Findings: Surgical and trauma care capacities increased with higher levels of care. The median PIPES score was significantly higher for tertiary facilities than primary and secondary facilities [13.8 (IQR 9.5, 18.2) vs. 4.7 (IQR 3.9, 6.2), p = 0.03]. The lower-level facilities were mainly lacking in personnel and procedures. Conclusions: Surgical and trauma care capacities at healthcare facilities in Haryana, India demonstrate a shortage of surgical resources at lower-level centers. Specifically, the Primary Health Centers were not operating at full capacity. These results can inform resource allocation, including increasing education, across different facility levels in rural India.